2021
DOI: 10.1097/wad.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Relative Experiences and Decision-making About Genetic Testing and Counseling for Familial ALS and FTD

Abstract: Genetic testing and counseling is an emerging part of care for patients with amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) and their families. This scoping review aimed to map patients’ and relatives’ experiences of genetic testing and counseling for familial ALS and FTD and the factors influencing their decision to proceed with testing or counseling. Informed by the Joanna Briggs Institute methodology, 5 databases were systematically searched. Thirty studies from 39 references were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 92 publications
(497 reference statements)
1
19
0
Order By: Relevance
“…42 Studies facing this complexity using comprehensive measures of outcomes in large cohorts of at-risk individuals are warranted. 39 In conclusion, the results of our clinical series of at-risk relatives from families with inherited AD and FTD showed that the decision to undergo a structured protocol of predictive genetic testing was not harmful as measured on a broad range of psychological outcomes, and might be beneficial on life planning and depressive symptoms. However, several uncertainties remain.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…42 Studies facing this complexity using comprehensive measures of outcomes in large cohorts of at-risk individuals are warranted. 39 In conclusion, the results of our clinical series of at-risk relatives from families with inherited AD and FTD showed that the decision to undergo a structured protocol of predictive genetic testing was not harmful as measured on a broad range of psychological outcomes, and might be beneficial on life planning and depressive symptoms. However, several uncertainties remain.…”
Section: Discussionmentioning
confidence: 75%
“…One of 2 carriers who withdrew after genetic disclosure experienced elevated distress, as already reported in FTD cases. 39 The carrier who was lost to T6 did not declare the reason of withdrawal, but feelings associated with intrusion and avoidance were reported at 1-month follow-up. According to the principle of patient autonomy and to the nondirective approach of genetic counseling (Jamal et al 40 for a recent review), we did not attempt to persuade the participant to follow-up, nor were justifications required if the participant declined the invitation to follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with prior studies describing the unique challenges of the FTD caring experience [ 31 ] and a greater burden [ 32 ] and distress [ 11 ] in caregivers of people with FTD compared to those with Alzheimer’s disease. Furthermore, behavioural changes have also been associated with caregiver depression in those caring for people with FTD [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although carers described mixed feelings about testing and disclosure, they acknowledged that knowing about the condition prior to diagnosis was helpful in preparing to manage expectations of their future together, and facilitated a process of accepting the diagnosis and adjusting to the carer role. A systematic review by Crook et al (2021) found that while no studies specifically assessed the experience of genetic testing in fFTD, the wider FTD literature suggests that the carers and relatives of those with FTD often carry the responsibilities of providing consent on behalf of the patient and notifying family of the test results [ 33 ].…”
Section: Discussionmentioning
confidence: 99%